Hubungan antara Minat Belajar dengan Hasil Belajar Matematika Siswa Kelas VIII pada Materi Perbandingan - Diana, Erika; Syafri, Fatrima Santri (Polinomial : Jurnal Pendidikan Matematika, 2026)
This study was undertaken to ascertain the extent of the association between learning interest and mathematics achievement among eighth-grade students on the topic of proportion at SMP Negeri 21 Kota Bengkulu. The researcher employed a quantitative paradigm with a correlational design. A cohort of 28 students was designated as the sample through purposive sampling. Data were amassed using a learning-interest questionnaire adapted from Herdiyanto (2019) and a mathematics achievement test. The analytical procedure encompassed both descriptive and inferential statistics, preceded by prerequisite examinations comprising normality and linearity tests, followed by Pearson’s correlation analysis. The findings revealed that learning interest exhibits a remarkably strong and statistically significant nexus with students’ mathematics outcomes (r = 0.971; p < 0.05). These results underscore that learning interest contributes substantially to students’ academic attainment in the topic of proportion. Consequently, the study advocates that educators intensify strategies aimed at cultivating students’ learning interest to bolster their academic performance.